Expansion and functional diversification of long-wavelength-sensitive opsin in anabantoid fishes - Gerwin, Jan; Torres-Dowdall, Julián; Brown, Thomas F.; Meyer, Axel (Journal of molecular evolution, 2024)
Gene duplication is one of the most important sources of novel genotypic diversity and the subsequent evolution of phenotypic diversity. Determining the evolutionary history and functional changes of duplicated genes is crucial for a comprehensive understanding of adaptive evolution. The evolutionary history of visual opsin genes is very dynamic, with repeated duplication events followed by sub- or neofunctionalization. While duplication of the green-sensitive opsins rh2 is common in teleost fish, fewer cases of multiple duplication events of the red-sensitive opsin lws are known. In this study, we investigate the visual opsin gene repertoire of the anabantoid fishes, focusing on the five lws opsin genes found in the genus Betta. We determine the evolutionary history of the lws opsin gene by taking advantage of whole-genome sequences of nine anabantoid species, including the newly assembled genome of Betta imbellis. Our results show that at least two independent duplications of lws occurred in the Betta lineage. The analysis of amino acid sequences of the lws paralogs of Betta revealed high levels of diversification in four of the seven transmembrane regions of the lws protein. Amino acid substitutions at two key-tuning sites are predicted to lead to differentiation of absorption maxima (λmax) between the paralogs within Betta. Finally, eye transcriptomics of B. splendens at different developmental stages revealed expression shifts between paralogs for all cone opsin classes. The lws genes are expressed according to their relative position in the lws opsin cluster throughout ontogeny. We conclude that temporal collinearity of lws expression might have facilitated subfunctionalization of lws in Betta and teleost opsins in general.